Association of Profile Characteristics of Rice Growers and Adoption of Recommended Package of Practices (Indian Journal of Extension Education, 2019)
Rice (Oryza sativa L.) is one of the most important cereal grains in the world today and serves as a staple food source for more than half of the world’s population In Konkan region the area is about 0.44 million hectares with a production of about 15.10 lakh tons in the year 2013-2014 and for the region the package of practices of rice cultivation is being recommended by DBSKKV, Dapoli since 1972. The present study was conducted in Palghar district of Konkan region of Maharashtra state. Six villages from each of the two tehsils namely Wada and Palghar were selected purposively for this study on the basis of maximum area under cultivation of rice crop. From each selected village 10 rice growers were selected from making a total sample of 120 farmers. The data were collected through personal interview method. The extent of adoption of recommended rice cultivation technology by the farmers was at medium level. The annual income, extension contact, input availability, knowledge level were found associated with adoption level.